2021
DOI: 10.1155/2021/8186877
|View full text |Cite
|
Sign up to set email alerts
|

GDF‐11 Protects the Traumatically Injured Spinal Cord by Suppressing Pyroptosis and Necroptosis via TFE3‐Mediated Autophagy Augmentation

Abstract: Spinal cord injury (SCI) refers to a major worldwide cause of accidental death and disability. However, the complexity of the pathophysiological mechanism can result in less-effective clinical treatment. Growth differentiation factor 11 (GDF-11), an antiageing factor, was reported to affect the development of neurogenesis and exert a neuroprotective effect after cerebral ischaemic injury. The present work is aimed at investigating the influence of GDF-11 on functional recovery following SCI, in addition to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 78 publications
(78 reference statements)
1
17
0
Order By: Relevance
“…The outcomes demonstrated that SS-31 substantially reduced the expression levels of proteins associated with pyroptosis following SCI. Our group has previously explored the involvement of autophagy in SCI [ 7 , 61 , 62 ]. Basal levels of autophagy are vital for maintaining cell homeostasis and are required for neural cell function and survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The outcomes demonstrated that SS-31 substantially reduced the expression levels of proteins associated with pyroptosis following SCI. Our group has previously explored the involvement of autophagy in SCI [ 7 , 61 , 62 ]. Basal levels of autophagy are vital for maintaining cell homeostasis and are required for neural cell function and survival.…”
Section: Discussionmentioning
confidence: 99%
“…These investigations demonstrated that SS-31 increased autophagic flux in SCI. Previous research has demonstrated that activating autophagy in the context of CNS trauma inhibits the pyroptotic death of cells [ 7 , 61 , 65 ]. The results of our experiments corroborated these observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, the conventional neuroprotective therapies for CNS injury mainly attempt to relieve mechanical compression by surgery combined with hyperbaric oxygen therapy, high-dose methylprednisolone, nerve dehydration and other comprehensive programmes [ 6 8 ]. Basic research has revealed potential treatments such as growth factors, tissue engineering, cell transplantation and neuroinflammation inhibitors [ 9 – 11 ], but major breakthroughs have not yet been achieved. Although these therapeutic measures alleviate the loss of neurological function to a certain extent, the long-term prognosis of CNS injury and the recovery of neurological function are still not optimistic.…”
Section: Introductionmentioning
confidence: 99%